A facile one-pot domino reaction for the stereoselective synthesis of acryl derivatives promoted by Ca(OTf)2. Issue 19 (11th May 2016) - Yaragorla, Srinivasarao; Saini, Pyare Lal; Pareek, Abhishek; Almansour, Abdulrahman I.; Arumugam, Natarajan
Graphical abstract: Highlights: A unique catalytic system to access three classes of acryl derivatives. Isolation by simple filtration (no column chromatography required). This one-pot multicomponent reaction endures the step economy and atom economy. Simple reaction conditions. Ca(OTf)2 is used as an alternative to expensive transition metal catalysts. Abstract: A facile one-pot domino reaction for the stereoselective synthesis of acryl derivatives has been reported using alkaline earth catalyst [Ca(OTf)2 ]. Initially aryl amine reacts with ethyl propiolate to form β-enamino ester which further reacts with aryl aldehyde and indole in the presence of Ca(OTf)2 to give indolyl acrylates. It is interesting to note that in the absence of indole the reaction leads to the formation of benzylidene bisacrylates. Similarly β-enamino ester reacts with another electrophilic partner isatin in the presence of Ca(OTf)2 to give oxindolyl acrylates. The products were isolated in good yields by simple filtration.